2015
DOI: 10.2337/dc15-0641
|View full text |Cite
|
Sign up to set email alerts
|

The Presence and Consequence of Nonalbuminuric Chronic Kidney Disease in Patients With Type 1 Diabetes

Abstract: OBJECTIVE This study investigated the prevalence of nonalbuminuric chronic kidney disease in type 1 diabetes to assess whether it increases the risk of cardiovascular and renal outcomes as well as all-cause mortality. RESEARCH DESIGN AND METHODS This was an observational follow-up of 3,809 patients with type 1 diabetes from the Finnish Diabetic Nephropathy Study. All patients were Caucasians and thoroughly examined at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 31 publications
6
42
3
1
Order By: Relevance
“…In line with this, cohort studies, including prepubertal children with average diabetes duration of 5–8 years, revealed glomerular base membrane thickening and mesangial expansion [16], while they also disclosed that long-standing nonalbuminuric T1D participants might have significant glomerulopathy lesions [1719, 21]. Moreover, the prevalence of nonalbuminuric CKD in T1D was recently reported to be 2% and was associated with a higher risk of cardiovascular morbidity as well as all-cause mortality in people with T1D [4, 5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, cohort studies, including prepubertal children with average diabetes duration of 5–8 years, revealed glomerular base membrane thickening and mesangial expansion [16], while they also disclosed that long-standing nonalbuminuric T1D participants might have significant glomerulopathy lesions [1719, 21]. Moreover, the prevalence of nonalbuminuric CKD in T1D was recently reported to be 2% and was associated with a higher risk of cardiovascular morbidity as well as all-cause mortality in people with T1D [4, 5]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, it represents a significant burden to the patients and the society they live in [2, 3]. Moreover, nonalbuminuric DN has been reported to have a prevalence of 2% among people with T1D and chronic kidney disease (CKD) [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Up to 20% of patients with type 2 diabetes already have diabetic kidney disease when diagnosed with diabetes and a further 30% to 40% develop DN, mostly within 10 years of diagnosis . Nonalbuminuric DN is less studied, but a recent study from Finland reported that 2% of patients with T1D had nonalbuminuric CKD …”
Section: Prevalence and Incidence Of Dn In T1dmentioning
confidence: 99%
“…Full‐text articles were screened to capture the relevant data for patients with T1D who had DN without age limits (Table ). Our inclusion criteria were as follows: Article was published as a peer‐reviewed research article, patients developed DN as a complication of T1D only, patients were of Arab ethnicity and lived in Arab countries, and patients developed nephropathy as measured by microalbuminuria or macroalbuminuria or by reduced glomerular filtration rate. Our exclusion criteria were as follows: It was unclear whether patients developed nephropathy because of T1D or T2D, nephropathy resulted from T2D only, the type of diabetes was not mentioned in the study, lack of random selection of the T1D subjects, and publication in a language other than English.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies showed that DN, in some cases, begins prior to the onset of albuminuria. In addition, it has been reported that some of patients with T1D had nonalbuminuric nephropathy . Therefore, several studies have proposed the use of new phenotypes such as the early renal function decline together with MA …”
Section: Introductionmentioning
confidence: 99%